THE ESTABLISHMENT OF PANCASILA AS THE GROUNDING PRINCIPLES OF INDONESIA - Megawati Soekarnoputri (Jurnal Pertahanan: Media Informasi ttg Kajian & Strategi Pertahanan yang Mengedepankan Identity, Nasionalism & Integrity, 2021)
Grounding Pancasila is the driving force and energy to make Pancasila in the concept of political, economic, social, cultural, as well as mental and spiritual development. The study aims to analyze the power of Pancasila as a basic assumption of Indonesian to respond to recent challenges faced by this country. This study employs a deconstruction approach that aims to describe how Pancasila become Indonesia's Basic Principles. The historical methods are heuristics, verification, interpretation, and historiography. Sources of data obtained are reading Soekarno's thoughts through his work "Under the Flag of Revolution". Soekarno's formulation of Pancasila thought was rooted in a sense of nationalism that wishes the Indonesian people to live side by side in peace and prosperity, and integrate all elements. This study concludes that as a basic philosophy (philosophische grondslag), Pancasila becomes a basic guideline for the Indonesian people in looking at the reality of the universe, humans, society, nation, and state about the meaning of life and the basis for Indonesian people to solve problems faced in life and our existence.